Strategic Decision-Making Analysis on Product Prioritization at Batterspoon By Mulia Using Analytic Hierarchy Process (AHP) - Farah Fabriana (Green Publisher Indonesia, 2026)
Write abstract in Bahasa Indonesia here. The font size is 12 and not bold. The first sentence of the abstract should be 3 spaces away from the last line of the program name. The abstract content, which is an Indonesian translation of the abstract in English language, is printed in size 1; not bold; and in italic form. The first word or the beginning of a new paragraph is separated by a single space from the last sentence of the preceding paragraph. Abstract are written in Indonesian and consist of 500-800 words. The end of abstract, which is still in the sheet of this abstract but in separate line from abstract, ended with keyword. Keywords written at the bottom the abstract are words which are related and derived from the abstract, and SHOULD NOT BE derived / taken from the body / text project thesis. The minimum numbers of keywords are 4 single words or a single meaningful two-word combination and maximum number of keywords are 7 single words or a single meaningful two-word combination.